Fabricação e caracterização elétrica de células solares a partir de filmes finos orgânicos - Braunger, Maria Luisa [UNESP] (2015)
In the area of organic photovoltaics, there is a continuous effort to improve the efficiency of the devices. In order to reach this goal. it necessary to evaluate the characteristics that influence their performance...